The Portrayal of EFL Preservice Teachers’ Engagement in A Video Stimulated Reflection in Teaching Practicum - Novitasari, Devi; Rahman, Abd. (Universitas Muhammadiyah Mataram, 2024)
Using a video to reflect teaching practice in EFL settings has been widely investigated. However, EFL preservice teachers’ engagement in video stimulated reflection (VSR) process in teaching practicum context has been under researched. To fill this gap, this study aims to examine how EFL preservice teachers engaged in VSR during their teaching practicum. The phenomenological approach combined with the case study was used to make sense of EFL preservice teachers’ experience in reflecting their teaching practices stimulated by video during their teaching practicum. Data of the study were garnered from EFL preservice teachers’ multiple reflective writings. To ensure the accuracy and to avoid misinterpretation of the data, member checking was done. Engagement framework proposed by Bowden and Naumann was used as an analytical tool of the present study. The findings of the study revealed that EFL preservice teachers were cognitively, emotionally, socially and behaviorally engaged in video-stimulated reflection during their teaching practicum. These empirical findings provide insighs that EFL preservice teachers’ behavioral, emotional, social and cognitive engagement can be promoted through VSR that is crucial to improve their teaching quality. Recommendation and future studies are also discussed.